The Use of Reference by the Characters in Midnight in Paris Movie - Rangga Satya Ramadhan Bratha Sena; Andang Saehu; Udayani Permanaludin (Institut Agama Islam Negeri Palopo, 2022)
In a conversation, it must have a meaning or purpose in the form of a message and it is interrelated. This study aims to identifying the reference categories that are often used and to analyze the construction of reference in film Midnight in Paris. The method used in this study is a qualitative approach that use descriptive analysis. The data collected from the film were then analyzed descriptively. The result shows that the most dominant type of reference used in film is Name and referent. In a film the mention of a name either a place name or a person's name is a normal and frequent phenomenon moreover that 'name' would be the best word to use in order to make identify or refers to something or someone successful and from a person's name and place name. It can refer or interpret the meaning intended in a person's utterance to the listener. Furthermore, a listener or reader can find out the intent of the speaker or the sender of the message which must have a relationship with each other. Furthermore, the researcher found that the way to construct the reference in the movie is by looking at the nouns or verbs that are present in the conversation, such as proper names, indefinite nouns or definite nouns, if in the sentence there are elements that have been mentioned, it can be said that the sentence is said included in the reference.Keywords: message; meaning;reference;identify